Political Connection and Real Earnings Management in Nigeria - Ahmad Haruna Abubakar; Peter U Anuforo; Dahiru Hussaini; Musa Isa (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2021)
There is currently exists an important question on whether firm’s political network affect the level of their earning information. The aim of this study is to examine the influence of political connection on real earnings management. The analyses involve a sample of 72 non-financial firms with 360 firm-year observations for a five-year period (2014-2019). Data was obtained from the annual reports of these companies as well as from Thompson Reuters and Bloomberg databases. The Panel Corrected Standard Error was used to test the model studied. The finding shows that firms board with political connection are possible to have earnings manipulation which deteriorate the earnings quality. Thus, this study recommends that increased attention should be given to internal control mechanisms to help curtail corporate earnings manipulations, reduce the effect of political connection, and enhance the financial reporting quality.